Progress and prospect of polysaccharides as adjuvants in vaccine development - Xinlong Liang; Jiaying Zhou; Mengmeng Wang; Jing Wang; Houhui Song; Yigang Xu; Yuan Li (Virulence)
Vaccines are an effective approach to confer immunity against infectious diseases. Modern subunit vaccines offer more precise target and safe protection compared to traditional whole-pathogen vaccines. However, subunit vaccines require adjuvants to stimulate the immune system due to the less immunogenicity. Adjuvants strengthen immunogenicity by enhancing, modulating, and prolonging the immune response. Unfortunately, few adjuvants have sufficient potency and low enough toxicity for clinical use, highlighting the urgent need for new vaccine adjuvants with the characteristics of safety, efficacy, and cost-effectiveness. Notably, some natural polysaccharides have been approved as adjuvants in human vaccines, owing to their intrinsic immunomodulation, low toxicity, and high safety. Natural polysaccharides are mainly derived from plants, bacteria, and yeast. Partly owing to the difficulty of obtaining them, synthetic polysaccharides emerged in clinical trials. The immune mechanisms of both natural and synthetic polysaccharides remain incompletely understood, hindering the rational development of polysaccharide adjuvants. This comprehensive review primarily focused on several promising polysaccharide adjuvants, discussing their recent applications in vaccines and highlighting their immune-modulatory effects. Furthermore, the future perspectives of polysaccharides offer insightful guidance to adjuvant development and application.